Apartheid Afterlives: Imagining Freedom in the Aftermath of Racial Oppression in Cape Town, South Africa. Issue 1 (2nd January 2018) - O'Connell, Siona
Abstract: South Africa in 2018 finds itself at yet another crossroads with a changing of the presidential guard set against a backdrop of protests, state capture and a growing disenchantment afforded by the euphoria and promise of 1994, the year of the first democratic elections. This article considers the contemporary South African moment through the lens of the photographic archive of the racially oppressed who were subject to forced removals in Cape Town. It poses questions about the aftermath of racial oppression, representation and the nexus of history, the human and freedom.